Assessment of efficiency of the topical anesthesia at blockade of a nasopalatal nerve (LLC "Endo Press", 2020)
Hypothesis. Topical blockade at the level of the lower nasal passage for anesthesia of the upper incisors is a real hypothesis. Aim. Evaluate the effectiveness of topically anesthetics through the definition of pain thresholds using elektroodontotesting. Design. In a randomized, blind, crossover study included 25 volunteers 18 men and 7 women aged 19-23 years. Aerosol formulations were tested : 20% benzocaine, 15% lidocaine and 15% lidocaine with pre applique 0.1% solution of epinephrine, as well as a 2% solution of tetracaine , which were introduced in the lower nasal passage on a cotton swab for 1 min. Determined pain threshold of the upper central incisor using electrically testing before and after 5, 10, 20 min. infusion. Results. Pain threshold after administration of anesthetics increased from 4 to 16 microamperes . The presence of adrenaline with 15% lidocaine bringing the pain threshold to 26 microamperes. Conclusion. Application blockade of NPN in the nasal cavity, obtained using 4 topical anesthetics acted as a weak conduction anesthesia in relation to the Central upper incisors.